Pest potencial of Sitophilus zeamais on Brazil nut under storage conditions (Bioscience Journal, 2020)
The Brazil nut, fruit of Bertholletia excelsa H.B.K., a native plant of the Amazon region and may be considered one of the main extractivist products of countries like Bolivia, Colombia, Guyana, Venezuela, Peru and Brazil. In Brazil this plant can be found in the states of Acre, Amapá, Amazonas, Mato Grosso, Pará, Rondônia, Roraima and Tocantins. Species of the Coleoptera and Lepidoptera, have been classified as pest potentials of Brazil nut under storage conditions. Sitophilus zeamais (Coleoptera: Curculionidae) is one of the main insect pests attacking grain stores worldwide. This specie may be observed attacking grains in the field and in storage facilities (cross-infestation), presenting a wide variety of hosts. The purpose of this study was to assess the potential of adults of this species feed on Brazil nuts, and also to identify the type of injury as well as the life span of this coleopteran exposed to the meat of the Brazil nut. No feeding injury was observed on the surface of Brazil nuts and the life span of the insects was similar in treatments both with and without this food source in all populations evaluated. Due to the fact that S. zeamais adults do not injure, or feed on the Brazil nut, this beetle is not able to colonize this product and therefore may be considered a non-pest insect for stored Bertholletia excelsa almonds stored.